1983
DOI: 10.1042/bj2130513
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dolichol and dolichyl phosphate phosphatase from soya beans (Glycine max)

Abstract: A series of polyprenols, ranging in length from 15 to 22 isoprene units, has been isolated from soya beans (Glycine max) and purified by high-pressure liquid chromatography. N.m.r., i.r. and mass spectra of the compounds indicated that they are alpha-saturated polyprenols of the dolichol type. The amount present in dry seeds was about 9 mg/100 g, whereas dolichyl phosphate (Dol-P) was present only in trace amounts. Dol-P phosphatase activity was detected in the microsomal fraction of 5-day-old germinating soya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…A more detailed examination, together with progress in the development of a new chromatographic 2-D TLC technique (22), showed that this simplified polyprenol vs. dolichol dichotomy is, in fact, far more complicated. Dolichols were found as the predominant form in shoots (23) and seeds (24) of dicotyledonous plants. Small amounts of dolichols were also observed in young roots of Hevea brasiliensis.…”
mentioning
confidence: 99%
“…A more detailed examination, together with progress in the development of a new chromatographic 2-D TLC technique (22), showed that this simplified polyprenol vs. dolichol dichotomy is, in fact, far more complicated. Dolichols were found as the predominant form in shoots (23) and seeds (24) of dicotyledonous plants. Small amounts of dolichols were also observed in young roots of Hevea brasiliensis.…”
mentioning
confidence: 99%
“…In various model plant systems, including Arabidopsis thaliana, Glycine max (soybean), and Coluria geoides , as well as common plants such as magnolia, spinach, parsley, and perilla, the length of most dolichol molecules falls within the range of 14-18 isoprene units [125-128]. Interestingly, dolichols found in soybean seeds contain one additional isoprene unit compared to those in the roots, shoots, and leaves, which typically have 16 – 17 isoprene units [127].…”
Section: Eukaryotamentioning
confidence: 99%
“…followed according to Rip et al (1981) and Ravi et al (1983). The assay contained a final concentration of 100 mM Tris-maleate, pH 7.4, 0.05% (w/v) Triton X-100, 10 mM dithiothreitol, 10 mM EDTA, 10 pM [I-'~c]DO~-P (lo6 dpm/mL), and 75 pg/mL microsomal protein.…”
Section: Glycosyl Trans Ferasesmentioning
confidence: 99%